Finance and Development, December 2008. (Finance and Development; Finance and Development ;, 2008)
Cracks in the System: World Economy Under Stress" explores the rapidly changing institutional and policymaking landscape around a financial crisis that now threatens a deep and prolonged global recession. The lead article looks at how the world got into the mess and what to do about it, both now and over the medium term. Other articles review options for changing the rules of world finance, examine the case for modernizing the way countries coordinate their policies, and try to draw some lessons from past financial crises. The "other crisis" of high food and fuel prices is also assessed, as the effects extend past the mid-2008 price peak. "People in Economics" profiles Robert Shiller; "Picture This" illustrates how middle-income economies can reach high-income status; "Back to Basics" looks at all the components that make up gross national product; and "Country Focus" spotlights Saudi Arabia.